2006
DOI: 10.1002/app.23701
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the thermal degradation chemistry and flammability of commercial flexible polyurethane foams

Abstract: In this article, we report the use of a variety of analytical methods, in particular, solid-state 1H-NMR and 13C-NMR to characterize the relationship between the condensed-phase chemistry and burning behavior as determined by a series of combustion tests for two commercially derived flexible polyurethane foams, one combustion-modified. The combustion tests showed that the foams met several regulatory requirements in terms of their fire performance, whether or not they were combustion-modified. Both foams passe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…This result supports the manufacturer's information where FR-G-32 only contains halophosphate as FR additive that predominantly performs in the gas phase. FR-Y-36 and FR-LG-38 have a higher nitrogen content than the other foams in Table I, and this is an indication of the presence of melamine [27] as reported by the manufacturer. Good agreement is found between the chemical composition of polyurethane foams used in this research and those reported in the literature [28][29][30].…”
Section: Polyurethane Foams and Melts Tested In Hot Disk Experimentsmentioning
confidence: 99%
“…This result supports the manufacturer's information where FR-G-32 only contains halophosphate as FR additive that predominantly performs in the gas phase. FR-Y-36 and FR-LG-38 have a higher nitrogen content than the other foams in Table I, and this is an indication of the presence of melamine [27] as reported by the manufacturer. Good agreement is found between the chemical composition of polyurethane foams used in this research and those reported in the literature [28][29][30].…”
Section: Polyurethane Foams and Melts Tested In Hot Disk Experimentsmentioning
confidence: 99%
“…[16][17][18] The thermal degradation process and its relation to foam ignition have been studied with a variety of analytical and existing fire-test methods. [19][20][21][22] The thermal stability and ignition of a conventional polyurethane foam mainly depend on the composition. 23 When a polyurethane foam is subjected to heat, various polyurethane linkages are broken at different temperatures.…”
Section: Ignition Of Polyurethane Foamsmentioning
confidence: 99%
“…The LOI value of the MDI‐PUR‐FF is unexpectedly high for flame‐retardant‐free PUR‐FFs. Typically, LOI values are in the range of 17.0 O 2 % to 21.3 O 2 % . Both MDI‐based PUR‐FFs burn with high melt flow, but only the AIRCRAFT‐PUR‐FF shows burning drops.…”
Section: Resultsmentioning
confidence: 99%